Involvement of TLR2–TLR4, NLRP3, and IL-17 in pain induced by a novel Sprague-Dawley rat model of experimental autoimmune encephalomyelitis - Kwilasz, Andrew J.; Clements, Madison A.; Larson, Tracey A.; Harris, Kevin M.; Litwiler, Scott T.; Woodall, Brodie J.; Todd, Laurel S.; Schrama, Anouk E. W.; Mitten, Eric H.; Maier, Steven F.; Van Dam, Anne-Marie; Rice, Kenner C.; et al. (Frontiers in Pain Research, 2022)
Up to 92% of patients suffering from multiple sclerosis (MS) express pain, most without adequate treatment, and many report pain long before motor symptoms associated with MS diagnosis. In the most commonly studied rodent model of MS, experimental autoimmune encephalomyelitis (EAE), motor disturbances caused by EAE can interfere with pain testing. Here we characterize a novel low-dose myelin-oligodendrocyte-glycoprotein (MOG)-induced Sprague-Dawley (SD) model of EAE-related pain in male rats, optimized to minimize motor disturbances. Adult male SD rats were treated with increasing doses of intradermal myelin oligodendrocyte glycoprotein (MOG1-125) (0, 4, 8, and 16 µg) in incomplete Freund’s adjuvant vehicle to induce mild EAE. Von Frey testing and motor assessments were conducted prior to EAE induction and then weekly thereafter to assess EAE-induced pain and motor impairment. Results from these studies demonstrated that doses of 8 and 16 µg MOG1-125 were sufficient to produce stable mechanical allodynia for up to one month in the absence of hindpaw motor disturbances. In follow up studies, these doses of MOG1-125, were administered to create allodynia in the absence of confounded motor impairments. Two weeks later, rats began daily subcutaneous injections of the Toll-like receptor 2 and 4 (TLR2-TLR4) antagonist (+)-naltrexone [(+)-NTX] or saline for an additional 13 days. We found that (+)-NTX also reverses EAE-induced mechanical allodynia in the MOG-induced SD rat model of EAE, supporting parallels between models, but now allowing a protracted timecourse to be examined completely free of motor confounds. Exploring further mechanisms, we demonstrated that both spinal NOD-like receptor protein 3 (NLRP3) and interleukin-17 (IL-17) are necessary for EAE-induced pain, as intrathecal injections of NLRP3 antagonist MCC950 and IL-17 neutralizing antibody both acutely reversed EAE-induced pain. Lastly, we show that spinal glial immunoreactivity induced by EAE is reversed by (+)-NTX, and that spinal demyelination correlates with severity of motor disturbances. These findings characterize an optimized MOG-induced SD rat model of EAE for the study of pain with minimal motor disturbances. Lastly, these studies support the role of TLR2-TLR4, IL-17, and NLRP3 antagonists as potential treatments for MS-related pain and other pain-and inflammatory related disorders.